Retinopathy of Prematurity - a literature review - Zach, Małgorzata; Rzeźnik, Patrycja; Borowy, Aleksandra; Wołoszyn, Barbara; Guzowska, Julia; Stępień, Julia; Sobczyk, Maciej; Stachera, Weronika; Suchcicka, Wiktoria; Chajnowska, Aleksandra (Journal of Education, Health and Sport, 2025)
Introduction and purpose Retinopathy of prematurity (ROP) is a rare ophthalmological disease affecting prematurely born infants. The aim of this review is to provide a comprehensive review of ROP, with a focus on its pathogenesis, epidemiology, classification and treatment. State of knowledge Retinopathy of prematurity has been recognized for over 80 years. Since then, a standardized classification system: the International Classification of Retinopathy of Prematurity (ICROP) has been developed, with the most recent (third) revision published in 2005. Treatment options have evolved from cryotherapy to laser photocoagulation and intravitreal anti-VEGF injections. Surgical options, such as scleral buckling and vitrectomy are reserved for severe cases of ROP. Although the majority of ROP cases are mild and self-limiting, severe ones can lead to serious ophthalmic and non-opthalmic consequences. Early detection and treatment are therefore of critical importance. Conclusions Retinopathy of prematurity remains a significant global health concern. Effective prevention relies on careful administration of supplemental oxygen, with targets oxygen saturation levels between 90 and 94%, balancing the risks of ROP and mortality. That remains a challenge, primarily in middle- and low income countries. While various agents have been tested as explored as potential prophylactic therapies, further research is needed in this area. Therapeutic approaches have improved over time and are generally effective. Intravitreal anti-VEGF medications are now well-established in clinical practice, yet ongoing studies continue to evaluate and compare the efficacy and safety profiles of different drugs.